2017
DOI: 10.22159/ijpps.2017v9i7.17611
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Hesperidin on Carbon Tetrachloride Induced Liver Fibrosis in Rats

Abstract: Objective: Exposure to carbon tetrachloride leads to serious liver injury and fibrosis. This study was aimed to evaluate the hepatoprotective effects of hesperidin against carbon tetrachloride (CCl4)-induced liver fibrosis in rats compared with the reference drug silymarin.Methods: Wistar albino rats were divided into five groups, each of eight rats. Animals were allocated into a control group, corn oil group and fibrosis control group. The remaining two groups received in addition to CCl4, silymarin (100 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Moreover, the serum profile of these rats showed a significant elevation of cholesterol level, which could lead to the accumulation of the lipid droplets in the liver. These results were in accordance with the previous studies 41,42 . The ALT and AST activities showed no significant change compared to the control rats in addition to the dramatic depletion of albumin level.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, the serum profile of these rats showed a significant elevation of cholesterol level, which could lead to the accumulation of the lipid droplets in the liver. These results were in accordance with the previous studies 41,42 . The ALT and AST activities showed no significant change compared to the control rats in addition to the dramatic depletion of albumin level.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, HDL concentration significantly decreased by 47.97%. High levels of serum TC, LDL and TG, and lower concentration of HDL were induced with CCl 4 in rats, consistent with results recorded from previous studies [44,48]. The obtained results may be attributed to the increase of the non-essential fatty acids resulted from lipid peroxidation induced by CCl 3…”
Section: Effect Of Experimental Treatments On Bloodsupporting
confidence: 91%
“…Furthermore, destroying of lipidperoxidation of cell membranes due to the reaction of CCl 4 with O 2 forming CCl 3 O 2 • , which resulted in the elevation of liver marker enzymes activities i.e. ALT, AST and ALP in blood serum [42], MDA level elevation [43] and the significant increase of total cholesterol, triglycerides, LDL and significant decrease of HDL level [44].…”
mentioning
confidence: 99%
“…AbdelSttar et al [41] studied that hesperidin (3,5,7-trihydroxy flavanone-7-rhamnoglucoside) and a flavanone glycoside present abundantly in citrus fruits, significantly ameliorated carbon tetrachloride (liver fibrosis inducer) in rats based on its antioxidant, anti-inflammatory, antilipidemic, and anti-fibrotic activities. Ahmed et al [42] reported grape seeds (Vitis vinifera) extract contains flavonoids, polyphenols, anthocyanins, proanthocyanidins, procyanidins, and the stilbene derivative resveratrol bioactive phytochemicals that possess inhibitory activity on the fat-metabolizing enzymes, pancreatic lipase, and lipoprotein lipase.…”
Section: Weta Et Almentioning
confidence: 99%